Thermomechanical failure of a second rotor stage in small gas turbine of biogas powered - Sławiński , Daniel (Instal, 2020)
The impulse mode of operation and the supply of various types of fuels cause frequent failures even in the small gas turbines. The paper presents the ravages of second rotor stage failure in a gas turbine. The excessive thermal elongation rise caused by fuel change was indicated as the main cause. We applied nonlinear numerical analysis, preceded by thermodynamic calculations of the turbine and visual inspection of the effects of failure. Simulations were performed on undamaged blade geometry under load resulting from combustion: nominal fuel and the changed fuel. Thermodynamic calculations demonstrated a 70K increase in temperature using the changed fuel. The blade tip displacements demonstrated the possibility of abrasion. The amount of elongation of the blade with increasing pressure or rotation speed does not pose as much danger as the elongations caused by the increase in temperature. To maintain long-term and safe operation of a gas turbine, it is necessary to strictly observe the manufacturer’s guidelines regarding fuel composition. If during the operation of a gas turbine it is likely that it can be powered by various types of fuels, then the structure should have adequate effort reserves and working tolerances.
Keywords: gas turbine; blade; failure